A Defence of Environmental Stewardship. (1st August 2012) - Welchman, Jennifer
Abstract : Public recognition of the fragility of the natural systems on which present and future generations depend has prompted calls for the practice of environmental stewardship - calls widely criticised in the environmental ethics literature. Some argue that stewardship's historical associations entail that it is inherently sexist, speciesist and/or anthropocentric. Others argue that absent belief in a creator to appoint us as stewards and hold us accountable, talk of 'environmental stewardship' is empty. I review the concept's recent evolution and provide a tentative definition. I argue that so defined, it is not vulnerable to standard criticisms, but is instead a promising way of construing morally decent conduct towards the environment.